Potential Combination of Dayak onion Eleutherine palmifolia L. and Chrysanthemum flower Chrysanthemum indicum L. as Anti-aging: Network Pharmacology Approach - Fitriyani; Salsabila Eka Setia Ningrum; Roihatul Mutiah (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2024)
Background: An anti-aging agent is a preparation or product used to inhibit skin aging. Aging occurs because of cell damage caused by free radicals. Therefore, anti-aging agents, which contain antioxidants to inhibit oxidative stress caused by free radicals, are needed. Dayak onion (eleutherine palmifolia (L) Merr.) and chrysanthemum flowers (Chrysanthemum indicum L.) have high antioxidant content, which has the potential to inhibit aging. Objective: To determine the anti-aging potential of dayak onion and chrysanthemum flower compounds Methods: Network pharmacology was performed using GeneCards (https://www.genecards.org) to obtain target genes, Cytoscape v3.10.1 software (https://cytoscape.org), DisGeNET (https://www.disgenet.org), STRING (https://www.string-db.org/), and the Kyoto Encyclopedia of Genes and Genomes (KEGG) PATHWAY (https://www.genome.jp/kegg/pathway.html). Results: Based on Network Pharmacology, dayak onion and chrysanthemum flowers showed that 14 of the 200 target proteins were involved in biological processes and signaling pathways for premature aging syndrome. Conclusion: The combined compound from dayak onion and chrysanthemum flower has anti-aging activity due to seven bioactive components in the hydroxycinnamic acid group. This compound influences biological processes and longevity by regulating the CAD, SIRT1, and TP53 signaling pathways. Therefore, the combination of dayak onion and chrysanthemum flowers has potential as an anti-aging agent.